Race/Ethnicity, Perceived Skin Color, and the Likelihood of Adult Arrest. (October 2021) - Finkeldey, Jessica G.; Demuth, Stephen
Research has long-documented racial/ethnic disparities in criminal justice outcomes. However, despite race/ethnicity being a multidimensional social construct, prior research largely relies on self-identification measures, thereby disregarding research on skin tone stratification within-racial/ethnic groups. The current study extends beyond this by examining the relationship between race/ethnicity and arrest employing both self-identified race/ethnicity and perceived skin color. Using data from the National Longitudinal Study of Adolescent to Adult Health, we explore the main and intersecting effects of self-identified race/ethnicity and perceived skin color on experiencing an arrest in adulthood between- and within-self-identified Whites, Blacks, Latinos, Native Americans, and Asians. We use structural disadvantage as a framework for exploring how social structural factors as well as antisocial behavior mediate the relationship between race/ethnicity/color and arrest. Results suggest that focusing on the racial/ethnic disparities alone masks differences in arrest by color and that the effect of color varies by race/ethnicity. Results also suggest that measures indicative of disadvantage, but not offending, partially explain these associations.